Visions of death and re-creation: Ezekiel 8–11, 37:1–14 and the crisis of identity in the Babylonian exile and beyond. (October 2015) - Hiebel, Janina Maria
The words and images of death and re-creaction in Ezekiel refer to the collective identity of the House of Israel and to its relationship with its God. Two symptomatic texts are discussed: the first temple vision (Ezek 8–11) and the vision of the valley of bones (Ezek 37:1–14). From Ezek 8–11, the vision of the defiled temple, it becomes evident that the relationship between YHWH and Israel is in a crisis beyond repair; death and destruction are the consequences. The reality of death is the starting point of 37:1–14. The vision demonstrates YHWH's ability and willingness to restore life even to the dry, scattered bones and, thus, also to Israel as the people of YHWH. For the author(s) of these texts, the initiative for destruction lies on the human side first; the initiative for restoration lies with God alone. What dies and is resurrected is the relationship between God and God's people. Its 'death' becomes a threat to the identity of both. Its 're-creation' is not an act of mercy but an act of power, safeguarding YHWH's identity as well as Israel's. Ezekiel's contribution to overcoming the crisis of the Babylonian exile is not to be underestimated. These texts' potential to encourage hope is greater than commonly granted and they may hold a message also for our times.